A study on the mechanical and economic performance comparison of ceramsite concrete based on fiber selection and optimization - Shifang Wang; Zeyu Li; Le Fan; Zhicheng Zhang; Shi Yin; Ji Yuan; Haijie He; Hongjian Lin; Wei Lin; Xiongwei Dai; Wen Xu; Kaisheng Yu (Scientific Reports)
Abstract To improve the toughness and strength of ceramsite concrete, this study employed three different types of fibers to enhance its performance. It prepared 8 sets of specimens, conducted stress-strain curve and static strength tests, and calculated various performance parameters. Through analysis of the economic performance and failure modes, it is found that high-toughness polypropylene fibers and steel fibers significantly enhanced both the strength and toughness of ceramsite concrete, while carbon fibers, although capable of increasing strength, do not improve toughness. Specifically, high-toughness polypropylene (HTPP) fibers and steel fibers increased the strength of ceramsite concrete by 32.8% and 49.0%, respectively, resulting in corresponding improvements in strength-to-weight ratio by 33.0% and 39.8%. While the toughness index Wcu 0.85 increased by 20.0% and 85.1%, respectively, Wcu 0.5 increased by 29.0% and 257.6%. The failure mode exhibited ductile fracture. Additionally, HTPP fibers were more cost-effective in increasing the strength and toughness of ceramsite concrete. Finally, based on SEM test results, we explained the mechanisms through which the three types of fibers enhance the performance of ceramsite concrete from the perspective of fibers surface characteristics. These research findings provide theoretical support for the optimization design of ceramsite concrete and are of significant importance for its application as a structural material.